Studies on the microbial diversity of commercially important enzymes for enantioselective transformations on a new range of 4-aryl-1,4-dihydropyridine - Kaur, A.; Bansal, R.; Kaur, J. (Penerbit Universiti Kebangsaan Malaysia, 2013)
A new series of 4-aryl-1, 4-dihyropyridines possessing potent calcium channel blocking activity along with good vasodilatory profile by the modified Hantzsch condensation using trifluoroacetic acid as catalyst has been synthesized and reported from our laboratory. The present work describes chemo enzymatic approach for the enantioselective hydrolysis of a 1, 4-dihydropyridine skeleton. In this study, lipases have been recognized as very useful biocatalyst. Diverse range of organisms including bacteria, fungi have been studied for extracellular enzyme production. Growth of the organisms and lipase production were measured at various intervals of time. Lipases from all the sources were assayed for at various temperatures ranging from 15 to 45ºC and pH in the range of 3.0 to 9.0. Variation of enzyme activity with substrate concentration has also been investigated. The lipases from above sources have been studied for their potential of enantioselective catalysis with the newly synthesized dihydropyridine diesters to obtain enantiopure products. Optical yields were confirmed with the help of polarimeter and HPLC analysis is being studied presently. The methodology for higher yields will be developed which could lead to production of optically active calcium channel blockers.